Sarcoglottis wernerherzogii (Spiranthinae), a new species from Cusco, Peru : addenda - Collantes Meza, Benjamín
A comparative table between Sarcoglottis wernerherzogii, S. fasciculata, and other species of the genus present in Peru, is included.